Amyloidosis of the Lung - Khoor, Andras; Colby, Thomas V. (Archives of pathology & laboratory medicine (1976), 2017)
Context.—Amyloidosis is a heterogeneous group of diseases characterized by the deposition of congophilic amyloid fibrils in the extracellular matrix of tissues and organs. To date, 31 fibril proteins have been identified in humans, and it is now recommended that amyloidoses be named after these fibril proteins. Based on this classification scheme, the most common forms of amyloidosis include systemic AL (formerly primary), systemic AA (formerly secondary), systemic wild-type ATTR (formerly age-related or senile systemic), and systemic hereditary ATTR amyloidosis (formerly familial amyloid polyneuropathy). Three different clinicopathologic forms of amyloidosis can be seen in the lungs: diffuse alveolar-septal amyloidosis, nodular pulmonary amyloidosis, and tracheobronchial amyloidosis. Objective.—To clarify the relationship between the fibril protein–based amyloidosis classification system and the clinicopathologic forms of pulmonary amyloidosis and to provide a useful guide for diagnosing these entities for the practicing pathologist. Data Sources.—This is a narrative review based on PubMed searches and the authors' own experiences. Conclusions.—Diffuse alveolar-septal amyloidosis is usually caused by systemic AL amyloidosis, whereas nodular pulmonary amyloidosis and tracheobronchial amyloidosis usually represent localized AL amyloidosis. However, these generalized scenarios cannot always be applied to individual cases. Because the treatment options for amyloidosis are dependent on the fibril protein–based classifications and whether the process is systemic or localized, the workup of new clinically relevant cases should include amyloid subtyping (preferably with mass spectrometry–based proteomic analysis) and further clinical investigation.